(untitled) (Bangladesh Journal of Urology, 2020)
Self-inflicted foreign bodies in the male urethra and urinary bladder are an emergency that urologists may rarely have to face. A case of an electrical wire inserted in the male urethra and coiled in the bladder is presented here. A 33-year-old male presented with the inability to void and bloody urethral discharge after having introduced a long electrical wire in his urethra for masturbation 6 hours earlier. He had made several unsuccessful attempts to remove it. We know that variety of these objects may be impressive and removal of the foreign body may be quite challenging requiring imagination and high-level surgical skills. In this case an electrical wire was used and the diagnostic as well as the therapeutic steps for its removal are presented here. Bangladesh Journal of Urology, Vol. 14, No. 2, July 2011 p.62-64